Verification Analysis of the Ground Comprehensive Application Software for CMD System - 杨颖; 金炜东 (机车电传动)
Software verification was an important way to enhance the reliability of software products and to assure software to fullfill customer’s needs. In accordance with the high-reliability requirements of ground comprehensive application software for CMD system, the paper described the process of software verification implementation and the specific methods of designing test case in order to answer the question how to guarantee the effect of software verification.